1998
DOI: 10.1111/1475-6765.00389
|View full text |Cite
|
Sign up to set email alerts
|

Issue news and electoral volatility

Abstract: Abstract. This article shows that issue coverage in the media partly explains both the political landslide at the 1994 elections in the Netherlands and the political continuity in the 1994 elections in Germany. Theories of issue voting guided the research. Issue ownership theory maintains that voters will remember which party has the best record of solving problems in emphasized issue areas. Proximity models and directional models suggest that voters' own issue positions will be compared to the perceived issue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 16 publications
(22 reference statements)
1
12
0
1
Order By: Relevance
“…Thus, (a) when an issue received much attention in the media which a voter is exposed to, and (b) a voter considers a certain party to have the best solution for that issue, he or she will probably switch to that party. The results corroborate the assumptions of previous studies on an aggregate level (Kleinnijenhuis & De Ridder, 1998;Kleinnijenhuis et al, 2007) and suggest that issue ownership indeed underlies the effect of issue news on electoral volatility. The finding that issue news leads to vote switching challenges earlier findings by Takens (2013), who concluded that issue coverage stabilizes vote choice.…”
Section: The Impact Of Issues Party Visibility and Evaluations On Vsupporting
confidence: 89%
See 2 more Smart Citations
“…Thus, (a) when an issue received much attention in the media which a voter is exposed to, and (b) a voter considers a certain party to have the best solution for that issue, he or she will probably switch to that party. The results corroborate the assumptions of previous studies on an aggregate level (Kleinnijenhuis & De Ridder, 1998;Kleinnijenhuis et al, 2007) and suggest that issue ownership indeed underlies the effect of issue news on electoral volatility. The finding that issue news leads to vote switching challenges earlier findings by Takens (2013), who concluded that issue coverage stabilizes vote choice.…”
Section: The Impact Of Issues Party Visibility and Evaluations On Vsupporting
confidence: 89%
“…The missing link between issue news and volatility is thus the party: the impact of issue news on vote switching is dependent upon the issue discussed, because different issues are perceived to be owned by different parties. These assumptions have been tested on the aggregate level, looking at vote choice (Kleinnijenhuis & De Ridder, 1998;Kleinnijenhuis, Van Hoof, Oegema, & De Ridder, 2007;Sheafer & Weimann, 2005), but not on the individual level focusing on vote switching.…”
Section: Abstract Campaign News Content Analysis Media Effects Panmentioning
confidence: 99%
See 1 more Smart Citation
“…The NIPO telepanel is a representative sample of the Dutch public and has been the basis for numerous academic studies (e.g., Kleinnijenhuis & De Ridder, 1998;Kleinnijenhuis & Fan, 1999). While the total sample size had 1,025 respondents in both waves, panel mortality resulted in 817 respondents actually participating in both waves; all analyses below are based on these 817 respondents.…”
Section: Survey Datamentioning
confidence: 99%
“…La cuestión de la corrupción era una cuestión propia de la oposición: cuanto mas a menudo aparecía en los medios, aunque fuera vinculada a la actuación del gobierno socialista en su persecución, más reforzaba la metapreferencia por el cambio de gobierno, y por tanto la estrategia de la oposición (Kleinnijenhuis y De Ridder, 1998). Es difícil imaginar qué estrategia, discursiva, política o económica, podría haber evitado que los socialistas llegaran como perdedores a las elecciones de 1996, incluso si la recuperación de la economía hubiera sido percibida por los electores.…”
Section: Clase Preferencias Y Cuestionesunclassified